2022
DOI: 10.1136/bmjopen-2021-056143
|View full text |Cite
|
Sign up to set email alerts
|

Association of self-reported snoring and hyperuricaemia: a large cross-sectional study in Chongqing, China

Abstract: ObjectiveTo examine the relationship between self-reported snoring and hyperuricaemia in a large-scale population in Chongqing, China.SettingFace-to-face electronic questionnaire survey, physical examination and biological sample testing were conducted in 13 districts of Chongqing. Chongqing is a municipality in southwest China.ParticipantsIn this study, 23 308 Han ethnicity permanent residents aged 30–79 years were recruited. Individuals missing data were excluded, 22 389 subjects were included in final analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(66 reference statements)
0
2
0
Order By: Relevance
“… 33 In our study, we strongly recommended that patients quit alcohol, which may reduce SUA levels and lead to higher success rate in patients who could improve their habitual risk factors after CA. In fact, the previous study demonstrated that the frequency and degree of alcohol consumption was a risk factor for HU, 34 therefore both SR maintenance and reduction in alcohol consumption after CA were assumed to be causes of SUA reduction in the present study. However, risk management was not assessed during follow‐up in this study, thus further studies will be needed to clarify the relationship between clinical outcomes and risk management, including post‐CA SUA levels after CA.…”
Section: Discussionmentioning
confidence: 57%
“… 33 In our study, we strongly recommended that patients quit alcohol, which may reduce SUA levels and lead to higher success rate in patients who could improve their habitual risk factors after CA. In fact, the previous study demonstrated that the frequency and degree of alcohol consumption was a risk factor for HU, 34 therefore both SR maintenance and reduction in alcohol consumption after CA were assumed to be causes of SUA reduction in the present study. However, risk management was not assessed during follow‐up in this study, thus further studies will be needed to clarify the relationship between clinical outcomes and risk management, including post‐CA SUA levels after CA.…”
Section: Discussionmentioning
confidence: 57%
“…Hyperuricemia (HUA) is a typical chronic metabolism illness brought about by purine metabolism disorder and serum uric acid (SUA) excretion disorder and it is a risk factor for diabetes, metabolic syndrome, obesity, high cholesterol, cardiovascular and kidney disease, [ 7 , 11 , 12 ]. According to a meta-analysis study [ 13 ], the prevalence of HUA was 16.4% in the Chinese population from 2000–2019. Epidemiological studies show that HUA is not only a key risk factor for gout, but also closely related to the diseases mentioned above as well as malignant tumors.…”
Section: Introductionmentioning
confidence: 99%